New Year Lecture 2024 - Prof. Dr. Akosua Adomako Ampofo (New Year Lecture, 2024)
Each year, the Africa Multiple Cluster of Excellence starts its line of annual activities and events with the New Year Lecture open to the interested public, featuring prominent speakers who address questions and concepts central to the Cluster’s agenda. The fifth annual New Year was held by Prof. Dr. Akosua Adomako Ampofo, Professor for Gender Studies and African Studies at the University of Ghana, and was entitled: "Crazy Tings: Can we be true to an African Agenda and Survive in today's Academy?" About the Lecture: Music is experienced and understood as an integral part of our self identity; it is closely linked with personal memories and significant moments of history, it is a form of self-expression of who we how we feel. Taking a slice out of Nigerian singer Tems’ book, Prof. Ampofo employed Tems' song, "Crazy Tings", as a metaphor to evoke the image of the multiple crazy things that abound in the academy, which is situated in a crazy world. She also reflected on how we might seek an intellectual engagement that serves Global Africa’s interests while ensuring that we are not destroyed in the process, and can hopefully even thrive. THE LECTURE IS TRANSLATED IN BRITISH SIGN LANGUAGE!